2019
DOI: 10.1007/s11673-018-9892-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-Hourly Repositioning for Prevention of Pressure Ulcers in the Elderly: Patient Safety or Elder Abuse?

Abstract: For decades, aged care facility residents at risk of pressure ulcers (PUs) have been repositioned at two-hour intervals, twenty-four-hours-a-day, seven-days-a-week (24/7). Yet, PUs still develop. We used a cross-sectional survey of eighty randomly selected medical records of residents aged ≥ 65 years from eight Australian Residential Aged Care Facilities (RACFs) to determine the number of residents at risk of PUs, the use of two-hourly repositioning, and the presence of PUs in the last week of life. Despite 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 108 publications
2
26
0
2
Order By: Relevance
“…Results from multivariate analyses revealed that respondents-oriented factors are significant in the effective management of pressure ulcers. Sharp et al (2019) noted that Pressure ulcers continue to develop in elderly patients despite the 2-hourly repositioning. The study results agree with a study conducted by Bergstrom et al (2014), whose results found repositioning of patients significant in reducing pressure ulcers.…”
Section: Multivariate Analyses: Factors Influencing the Management Of Pressure Ulcers Among Nursesmentioning
confidence: 99%
“…Results from multivariate analyses revealed that respondents-oriented factors are significant in the effective management of pressure ulcers. Sharp et al (2019) noted that Pressure ulcers continue to develop in elderly patients despite the 2-hourly repositioning. The study results agree with a study conducted by Bergstrom et al (2014), whose results found repositioning of patients significant in reducing pressure ulcers.…”
Section: Multivariate Analyses: Factors Influencing the Management Of Pressure Ulcers Among Nursesmentioning
confidence: 99%
“…7 Assessment of pressure injury risk is standard practice in nursing homes, 8-10 but prevention has proved elusive. 11 There is limited evidence for pressure injury prevention, 12 with support surfaces and manual repositioning having been the focus. Highspeci cation foam alternatives to standard hospital foam mattresses were found to signi cantly reduce pressure injury incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Key elements of such preventive program measures should include: implementation of evidence‐based practices, evidence‐based product selection, provision of education to hospital staff by healthcare providers which can be performed through implementing evidence‐based prevention programs 10 . Despite best efforts, pressure ulcers (PUs) do still occur and patients are at risk for PU not only just in hospital but also once discharged home 11 . In the hospital, 89% of PUs occur in the ICU population 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Despite best efforts, pressure ulcers (PUs) do still occur and patients are at risk for PU not only just in hospital but also once discharged home. 11 In the hospital, 89% of PUs occur in the ICU population. 12 While prevalence of category I-IV PUs was 8Á0%, and the overall nosocomial PU prevalence was 4Á5%.…”
Section: Introductionmentioning
confidence: 99%